Concentration Of Cortisol Metabolites In Captive Sumatran Elephants At Elephant Conservation Facilities In Aceh - Rosa Rika Wahyuni; Sri Wahyuni; Al Azhar; Gholib Gholib (The Faculty of Veterinary Medicine of Syiah Kuala University, 2018)
This study was conducted to validate the DRG Cortisol ELISA EIA-1887 Germany kit for measure the concentration of stress hormone metabolites (cortisol) from the feces and its correlation to the stressor factor in captive elephants in PKG and CRU of Aceh. These factors are location, diet and presence of livestock. There is no special treatment, observation based on the activity, behavior or natural condition of the animals. The sampling technique was non invasive, fresh dung samples of each (±20 gram) were collected from 25 elephants in CRU and PKG. Feces taken in the morning (before the animals are bathed) along with the observation of animal behavior. All samples were collected and stored at -200C until the analysis process. The validation test are analytic (parallelilmsm) and biological validation test. The analytic test result (paralillsm), showed that the sample curve was not parallel to the standard curve, but crossed the standard curve. While the results of biological validation test, DRG Cortisol ELISA EIA-1887 Germany kit can measure the concentration of cortisol hormone feces of Sumatran elephant and able to describe the difference of cortisol concentration relation to physiological events (stress vs non-stress). The mean values of cortisol metabolite concentrations from PKG Saree (Komplek PKG and Hutan Seunapet), Sampoiniet CRU, Cot Girek, Das Peusangan, Meulaboh and Aceh Timur were (577 ng/g and 400 ng/g), 435ng /g, 419ng /g, 517ng / g, 401ng/g and 425ng /g. The measurement results correlate with the physiological conditions and observed factors.